Social work methods and skills : the essential foudation of practice - Healy, Karen, ....- (Basingstoke : Palgrave Macmillan, 2012)
A clearly framed and comprehensive introduction to practice methods, this important text explores how methods and skills can be combined to offer a versatile professional toolkit for practice. It interrogates the social work process within a range of settings, including working with involuntary clients, and within community and family settings.
Keywords: Sociaal werk ; methoden